Stable hydrogen and oxygen isotope studies of rainfall and streamwaters for two contrasting holm oak areas of Catalonia, northeastern Spain (Journal of Hydrology, 1992)
Results are presented of a study of stable hydrogen and oxygen isotopes in rainfall and streamwaters for the Montseny and Prades areas in northeastern Spain: results cover the full year of 1991. The isotopic pattern for rainfall is similar for both areas: there is a wide range in isotopic contents and the results show a strong, near-linear trend, 62H = 7.9 x 6~80 + 9.8 (N = 59; r 2 = 0.952), the 'local meteoric line'. There is slight curvature to the data which may be related to the sources of water vapour forming the rainfall. Within the streams, the isotopic variability is much less than that of the rainfall although the data lie on, or very near to, the meteoric line. Data for detailed collections during storm events show more scatter than those collected regularly on a fortnightly basis. The event data show a linear feature that conforms to the local meteoric line. These results indicate that: (1) the main supply of water to the stream stormflow comes from water stored in the catchment prior to the event; (2) waters of more than one isotopic composition reside within the catchment and are transferable to the stream during storm events; (3) the main process of water transfer from the catchment back to the atmosphere comes from transpiration by the trees and (possibly) complete evaporation from the near-surface soil horizons and the tree canopy; (4) the isotopic technique cannot be used for quantitative hydrograph separation in this instance at least two water types can be present within the catchment at any given time.